2006
DOI: 10.2337/diabetes.55.02.06.db05-0971
|View full text |Cite
|
Sign up to set email alerts
|

ACDC/Adiponectin Polymorphisms Are Associated With Severe Childhood and Adult Obesity

Abstract: Common single nucleotide polymorphisms (SNPs) in the ACDC adiponectin encoding gene have been associated with insulin resistance and type 2 diabetes in several populations. Here, we investigate the role of SNPs ؊11,377C>G, ؊11,391G>A, ؉45T>G, and ؉276G>T in 2,579 French Caucasians (1,229 morbidly obese and 1,350 control subjects). We found an association between severe forms of obesity and ؊11,377C (odds ratio 1.23, P ‫؍‬ 0.001) and ؉276T (1.19, P ‫؍‬ 0.006). Surprisingly, alternative alleles ؊11,377G and ؉276… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
151
3
7

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(181 citation statements)
references
References 27 publications
(22 reference statements)
20
151
3
7
Order By: Relevance
“…4,[25][26][27] Decreased adiponectin levels were described in weight-stable obese subjects. However, many studies have reported an association between obesity risk and hyperadiponectinemia associated with polymorphisms, 9,18,28 which were in accordance with our results. The physiological mechanisms to explain these results are a complex question to address.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…4,[25][26][27] Decreased adiponectin levels were described in weight-stable obese subjects. However, many studies have reported an association between obesity risk and hyperadiponectinemia associated with polymorphisms, 9,18,28 which were in accordance with our results. The physiological mechanisms to explain these results are a complex question to address.…”
Section: Discussionsupporting
confidence: 93%
“…According to previous studies 9, 18,19 we found standardized linkage disequilibrium between À11391 and À11377 SNPs. In this context, haplotype combinations could clarify associations involving these correlated markers.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations